Kesintasan Satu Tahun Pasien yang Menjalani Intervensi Koroner Perkutan Primer di Rumah Sakit Dr. Cipto Mangukusumo - Hamdan, Muhammad Afriadi; Wijaya, Ika Prasetya; Widhani, Alvina; Yamin, Muhammad (UI Scholars Hub, 2023)
Introduction. Primary percutaneous coronary intervention (PPCI) is an angioplasty (with or without a stent) performed immediately on the infarct-related artery without prior administration of fibrinolytics. Although PPCI is the reperfusion therapy of choice in ST-segment Elevation Myocardial Infarction (STEMI) patients, survival in post-PPCI patients still varied and research on its determinant factors still showed inconsistent results. This study aimed to determine the predictors of oneyear survival in patients undergoing PPCI at Dr Cipto Mangunkusumo General Hospital. Methods. This retrospective cohort study evaluated the medical records of patients who underwent PPCI at Dr. Cipto Mangunkusumo General Hospital from January 2014 to December 2019. The data collected included clinical parameters and demographic data from the PPCI registry. Patients’ outcomes were cardiovascular mortality, determined based on medical records or by contacting patients or their families by phone. Survival curves were created using the Kaplan Meier method and significance using the log-rank test. Multivariate analysis was performed using the Cox Proportional Hazard model. Results. A total of 220 patients who underwent PPCI were included in this study. The mortality rate was 11.82% and the one-year survival post-PPCI was 88.2%, with a mean survival of 10.7 (10.2-11.2) months. The highest mortality rate occurred in the first month post of PPCI, then mortality trend decresed in the 2nd month to one year. In multivariate analysis, age >60 years [p<0.001; HR 4.25 (1.93-9.37)], high serum creatinine [P=0.031; HR 2.41 (1.08-5.33)], and Killip score III-IV [p<0.001; HR 4.06 (1.83-9.00)] were significant prognostic factors. Conclusion. The predictors of one years survival patients post of PPCI are age, serum creatinine level, and Killip score.